2018
DOI: 10.1007/s00421-018-3866-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training intensity in electromyostimulation on human skeletal muscle

Abstract: Low-intensity NMES could increase MT, muscle fiber CSA, and muscle strength in healthy human skeletal muscles. However, the magnitude of increase is lower in low-intensity than in high-intensity NMES training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
0
21
1
2
Order By: Relevance
“…[ 16 ] As a result of NMES, a number of adaptation processes occur in skeletal muscles, [ 17 ] and in the function of the nervous system. [ 18 ] To maximize the effect of NMES, sufficiently intense exposure regimes [ 19 ] and/or a long course of stimulation (at least 4 weeks for athletes) are required. Based on this, a 5-day NMES course with a fairly moderate degree of exposure, as was the case in the above studies in patients after cardiovascular surgery, is quite likely to have a limited effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 ] As a result of NMES, a number of adaptation processes occur in skeletal muscles, [ 17 ] and in the function of the nervous system. [ 18 ] To maximize the effect of NMES, sufficiently intense exposure regimes [ 19 ] and/or a long course of stimulation (at least 4 weeks for athletes) are required. Based on this, a 5-day NMES course with a fairly moderate degree of exposure, as was the case in the above studies in patients after cardiovascular surgery, is quite likely to have a limited effect.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that the intensity of NMES in healthy has a positive correlation with muscle CSA. [ 19 ] Also NEMS in healthy people, with a course duration of up to 4 weeks, leads to an increase in the strength of stimulated muscles without their hypertrophy. [ 22 ] The NMES intensity in patients after cardiac surgery was significantly lower, [ 8 , 9 ] and the course duration was shorter, which explains our results.…”
Section: Discussionmentioning
confidence: 99%
“…Although several factors could explain this, such as the method of strength measurement, the current intensity, the physical activity level of the participants and the stimulation duration, we believe that the most important factor might be the current intensity. The evidence suggests that the intensity should be at a maximum tolerable level to maintain the MVC level for strengthening effect . However, we increased the current intensity relatively minimally until visible contraction of the muscle fibers to avoid muscle damage as a result of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that the intensity should be at a maximum tolerable level to maintain the MVC level for strengthening effect. 9,16,23 However, we increased the current intensity relatively minimally until visible contraction of the muscle fibers to avoid muscle damage as a result of sarcopenia. Therefore, our MVC level might not have reached the desired level for isometric strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…One of these reasons is; in our study, the training program was scheduled over a period of 6 weeks and with a total of 12 sessions, which may have been not enough to provide muscle strength gain. Because, it is suggested that more than six weeks of exercise training is needed to increase muscle strength (Natsume et al, 2018). Another reason can be due to the electrical stimulation of the skeletal muscle causing a series of events leading to rapid twitch type 2b fibers; a conversion, which gives slow-twitch type 1 fiber properties (Ward, 2009;Ward and Shkuratova, 2002).…”
Section: Discussionmentioning
confidence: 99%